Avaliação do desempenho do restaurador dinâmico de tensão frente aos afundamentos e elevações de tensão - Jesus, Daniel Maia Fonseca de (2006)
Nowadays, national and international electric utilities and end users are becoming more and more concerned about the quality of the electrical power. Such concerns are related with the occurrence of electric disturbances capable to effect the operation and the life expectance of equipments and devices, as well as affecting and interrupting varied industrial processes. Of the above mentioned phenomena, short-duration voltage variations deserve special attention once they are the disturbances that cause the largest damages to the consumers. As a consequence of that, there are several devices available that minimize the effects of such disturbances on the equipments. Among those devices, the Dynamic Voltage Restorer (DVR) represents a modern proposal for the solution of the problems caused by voltage sags and swells. In this work, three different system topologies for DVRs are analysed throughout computer implementations. Comparisons are made between these topologies, with focus on both the general performance and on the electrical power quality of the entire system.